2016
DOI: 10.1016/j.ejvs.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Editor's Choice – Management of Secondary Aorto-enteric and Other Abdominal Arterio-enteric Fistulas: A Review and Pooled Data Analysis

Abstract: Endovascular surgery, where appropriate, is associated with better early survival than open surgery for secondary AEFs. Most of this benefit is lost during long-term follow-up, implying that a staged approach with early conversion to in situ vein grafting may achieve the best results in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 190 publications
(26 reference statements)
2
78
0
5
Order By: Relevance
“…132 In a systematic review of the literature conducted in 2016, 216 studies representing 823 patients with AEnF were compiled. 134 Bleeding was the most common symptom (71.7%), followed by sepsis (39.7%) and haemorrhagic shock (33.1%). Allograft related re-intervention rates were found in up to 55% of patients after five years (Table 8).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…132 In a systematic review of the literature conducted in 2016, 216 studies representing 823 patients with AEnF were compiled. 134 Bleeding was the most common symptom (71.7%), followed by sepsis (39.7%) and haemorrhagic shock (33.1%). Allograft related re-intervention rates were found in up to 55% of patients after five years (Table 8).…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Prior studies have found that, among the aforementioned surgical techniques, in situ repair using a vein graft or prosthetic graft is associated with the lowest long-term mortality rates and lowest rates of sepsis, especially if the graft is covered with omentum. However, even in situ vein grafting for SAEF is associated with an in-hospital mortality rate of 32%, which is considerably higher than the 7% in-hospital mortality of endovascular treatment of SAEF (3,29). Despite decades of attempted improvement and development of novel techniques, morbidity and mortality associated with open surgical repair of SAEF remain major obstacles (28,(30)(31)(32).…”
Section: S202mentioning
confidence: 93%
“…Some of this benefit is lost when analyzing long-term outcome data, primarily due to the increased rates of recurrence and sepsis associated with some endovascular techniques. Despite this, long term survival rates still appear higher with endovascular management of SAEFs compared to open surgery (3).…”
Section: Mini-reviewmentioning
confidence: 97%
See 2 more Smart Citations